2017
DOI: 10.1016/j.jmbbm.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic parameter identification of human brain tissue

Abstract: Understanding the constitutive behavior of the human brain is critical to interpret the physical environment during neurodevelopment, neurosurgery, and neurodegeneration. A wide variety of constitutive models has been proposed to characterize the brain at different temporal and spatial scales. Yet, their model parameters are typically calibrated with a single loading mode and fail to predict the behavior under arbitrary loading conditions. Here we used a finite viscoelastic Ogden model with six material parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 43 publications
6
118
1
Order By: Relevance
“…In direct contrast, gray matter from the thalamus has also been found to be 1.3 times stiffer than the white matter found in the corpus callosum (Prange and Margulies, 2002). As a result, the proportions of gray and white matter must be consistent in order to accurately compare the stress relaxation response between different brain tissue samples (Budday et al, 2017;Boudjema et al, 2017;Finan et al, 2017;Jin et al, 2013;Prange and Margulies, 2002). In this study, samples were extracted from the same region of the brain while striving for a consistent anatomical structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In direct contrast, gray matter from the thalamus has also been found to be 1.3 times stiffer than the white matter found in the corpus callosum (Prange and Margulies, 2002). As a result, the proportions of gray and white matter must be consistent in order to accurately compare the stress relaxation response between different brain tissue samples (Budday et al, 2017;Boudjema et al, 2017;Finan et al, 2017;Jin et al, 2013;Prange and Margulies, 2002). In this study, samples were extracted from the same region of the brain while striving for a consistent anatomical structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors of this study could find no previous studies that examined the mechanical response of brain tissue after a TBI. Instead, the literature shows researchers who have studied brain tissue using both experimental and computational methods to evaluate the mechanical response of uninjured brain tissue subjected to compression, tension, and shear (Bentil and Dupaix, 2014;Budday et al, 2017;Darvish and Crandall, 2001;Hrapko et al, 2006;Jin et al, 2013;Miller and Chinzei, 2002;Rashid et al, 2013;Velardi et al, 2006;Zhao et al, 2018).…”
mentioning
confidence: 99%
“…Most of the experiments have been performed at low strain rates corresponding to low-speed phenomena such as tumor growth, surgical procedures, etc., while fewer studies have focused on high strain-rate conditions such as that of TBI. Recently, Budday et al [6,11] applied a sequence of loading modes to the same human brain specimen and characterized the loading-mode speci c regional and directional behaviors. They reported that brain material had a pronounced compression-tension asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In the eld of FE modeling, a great deal of literature has been dedicated to the macro mechanical and material modeling of the brain tissue (see e.g., [12{16]). However, given the anisotropic nature of white matter discovered as a result of applying the DTI technique and ber tractography in recent years, multi-scale models have gained considerable importance [6,17]. The relation between mechanical loading at a macroscopic head level and cellular damage at a microscopic level is a complex problem.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, detailed computational models have been successfully constructed from magnetic resonance (MR) images [28][29][30][31]. The constitutive modeling of soft biological tissues has also received considerable attention [32][33][34][35][36][37]. Due to the complexity of the mechanical response of the tissues, the material parameters reported in the literature differ by orders of magnitude [35,38].…”
mentioning
confidence: 99%